Odpowiedzi

2010-02-06T12:49:03+01:00
A) (n+2)(n+3)=n²+3n+2n+6=n²5n+6
b) (x-4)(x+4)→(wzór skróconego mnożenia)→x²-16
c) (7+y)(10-y)=70-7y+10y-y²=-y²+3y+70
d) (x-y)(x+y)→(wzór skróconego mnożenia)→x²-y²
e) (ab-1)(c+1)=abc+ab-c-1
f) (r²+8)(12-n)=12r²-nr²+96-8n
3 5 3
2010-02-06T12:49:19+01:00
A) n²+3n+2n+6=n²+5n+6
b) x²+16
c) 70-7y+10y-y²= -y²+3y+70
d) x²-y²
e) abc+ab-c-1
f)12r²-nr²+96-8n
Najlepsza Odpowiedź!
2010-02-06T12:49:26+01:00
A) (n+2) * (n+3) = n² + 3n + 2n + 6 = n²+5n+6
b) (x-4) * (x+4) = (x²-4²) = x²-16
c) (7+y) * (10-y) = 70 - 7y +10y-y² = y² + 3y+70
d) (x-y) * (x+y) = x²-y²
e) (ab-1) * (c+1) = abc + ab-c-1
f) (r²+8) * (12-n) = 12r²-r²n+96-8n
3 5 3